2014
DOI: 10.1186/1752-0509-8-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-gene identification for pancreatic cancer survival via doubly regularized Cox regression

Abstract: BackgroundRecent global genomic analyses identified 69 gene sets and 12 core signaling pathways genetically altered in pancreatic cancer, which is a highly malignant disease. A comprehensive understanding of the genetic signatures and signaling pathways that are directly correlated to pancreatic cancer survival will help cancer researchers to develop effective multi-gene targeted, personalized therapies for the pancreatic cancer patients at different stages. A previous work that applied a LASSO penalized regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…These findings were different from another study that identified higher expression of ITGA5, SEMA3A, KIF4A, IL20RB, SLC20A1, CDC45, PXN, SSX3, and TMEM26 genes associated with shorter survival, and B3GNT1, NOSTRIN, and CADPS lower expression associated with poor outcome (Haider et al, 2014). Gong et al (2014) analyzed the high-dimensional microarray data of pancreatic cancer patients with localized and resected PDAC using doubly regularized Cox regression model, and identified and verified the following pathways and genes to be directly correlated to pancreatic cancer survival: DENN-D4A, KLF13, zinc finger protein family genes (ZNF229, ZNF233, ZNF395, and ZNF432), immune phagocytosis pathway (CYBA), SLC family (SLC22A8, SLC8A3, SLC24A6), TRP (Ca 2+ ) ion transport pathway (TRPV5, TRPM6), KCNK (K + ) ion transport pathway (KCNK3, KCNK18), and TGFb core pathway (spermatogenesis signaling set PCYT1B gene).…”
Section: Discussioncontrasting
confidence: 94%
“…These findings were different from another study that identified higher expression of ITGA5, SEMA3A, KIF4A, IL20RB, SLC20A1, CDC45, PXN, SSX3, and TMEM26 genes associated with shorter survival, and B3GNT1, NOSTRIN, and CADPS lower expression associated with poor outcome (Haider et al, 2014). Gong et al (2014) analyzed the high-dimensional microarray data of pancreatic cancer patients with localized and resected PDAC using doubly regularized Cox regression model, and identified and verified the following pathways and genes to be directly correlated to pancreatic cancer survival: DENN-D4A, KLF13, zinc finger protein family genes (ZNF229, ZNF233, ZNF395, and ZNF432), immune phagocytosis pathway (CYBA), SLC family (SLC22A8, SLC8A3, SLC24A6), TRP (Ca 2+ ) ion transport pathway (TRPV5, TRPM6), KCNK (K + ) ion transport pathway (KCNK3, KCNK18), and TGFb core pathway (spermatogenesis signaling set PCYT1B gene).…”
Section: Discussioncontrasting
confidence: 94%
“…Hence, in order to provide more reliable and biologically meaningful results, the inclusion of a-priori biological knowledge into the models is mandatory. To address this issue, new penalized Cox methods based on the integration of genomic information have been recently proposed (Zhang et al, 2013 ; Gong et al, 2014 ; Sun et al, 2014 ). In such models, the genomic information is encoded by a network whose graph structure identifies a given relation (edges) between genes (nodes).…”
Section: Introductionmentioning
confidence: 99%
“…These explosively growing amount of highdimensional gene expression data can be divided into two types: static and time series. The static expression data are assumed to be independently and identically distributed (IID), and many statistical inference algorithms [ 1 - 8 ] have been developed to identify key genetic signatures and signaling pathways that are frequently altered in some diseases. Gene regulatory network plays a critical role in the cell's proliferation and differentiation, so, a comprehensive understanding of gene regulatory network (GRN) and regulatory components will help discover some drug targeted genes in cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%